Developing a Web-Based Information System for Sub-Districts in North Sulawesi - Rawis, Joulanda A.M.; Lengkong , Jeffry Sony Junus; Dotulung, Reza A. W.; Wuwungan, Hansje T.; Rambitan, Maya C.; Rattu, Olviane I. (JR Education, 2023)
This research aims to create an information system in sub-districts in North Sulawesi that can be used easily by sub-district officials to process sub-district data and information. This research uses the Prototype Cycle method which has five stages, namely Quick Plan, Modeling Quick Design, Construction of Prototype, Deployment Delivery & Feedback, and finally Communication. The results of the development of this information system have been created and tested for use. From the test results, it was found that the website-based information system in the Tataaran 1 sub-district, South Tondano sub-district, can be used as a forum for collecting data and information for sub-district officials and can help the community with information related to activities in the sub-district and is easily accessible to all levels of society.